Evaluating the effectiveness of land-use zoning for the protection of built heritage in the Bagan Archaeological Zone, Myanmar—A satellite remote-sensing approach. (November 2019) - Edwards, Ben; Frasch, Tilman; Jeyacheya, Julia
Highlights: Satellite remote sensing data indicates heritage land-use zoning works at Bagan. Control settlements expand more rapidly than Bagan heritage area. Wider trend is for urban expansion despite rural socio-economic issues. Informs UNESCO WHS ongoing management. Abstract: This paper analyses the effectiveness of land-use zoning for heritage protection in the Bagan Archaeological Zone, Myanmar. Bagan is one of the most significant archaeological sites in the world for Buddhist built heritage, and was inscribed on the UNESCO World Heritage List in 2019. Beginning in the 9th or 10th centuries some 2500 religious monuments were built within the 60 square kilometre area of Bagan, a centre of kingship, Buddhist learning, and monasticism. Following a devastating earthquake in 1975 Burmese and international attention began to be paid to the reconstruction and conservation of the monuments at Bagan, but with mixed success. In this paper, publicly available satellite data is analysed to evaluate one of the important, but hitherto un-evaluated, elements of the local conservation regime – land-use zoning to restrict urban development. By measuring the expansion of urban areas within the Bagan Archaeological Zone from 1987 to 2018, in comparison with control settlements beyond the archaeological area, we conclude that a restrictive zoning regime has controlled urban sprawl, and aided the conservation of the setting of Buddhist monuments.